Understanding poverty - Banerjee, Abhijit V.; Benabou, Roland; Mookherjee, Dilip (Oxford : Oxford University Press, 2006)
This volume brings together essays by 34 leading economists about important things they have learnt from their research that relate to poverty. These essays range from the impact of colonialism and globalization to the future of micro-credit and the quest for vaccines.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Poverty; Poor